Guatemala : Expenditure Reform in a Post-Conflict Country - World Bank (Washington, DC, 2013)
This report is the third in a series of joint Government-World Bank reviews designed support Guatemala's peace process (See report nos. 15352 and 16392). As this report was under preparation in late 1998, Guatemala faced an emergency caused by Hurricane Mitch and increasing macroeconomic pressures associated with expansionary monetary and fiscal policies. Macroeconomic conditions continued to weaken in 1999, exacerbated by a number of external shocks, inappropriate macro policies and a fragile financial system. The success of the privatization program, in turn fed fiscal illusion, which was especially hard to resist in an electoral year. The availability of relatively large privatization proceeds created a sense that the emerging macroeconomic imbalances could be tolerated, peace and electoral outlays could be financed without the need to adopt revenue measures, and that international reserves were adequate to defend the Quetzal and keep inflationary pressures under control. While the original intention of this report was to analyze the fiscal stance supporting the peace process, progress in the Government's state modernization program, and performance in meeting agreed socioeconomic peace targets, the macroeconomic developments and the possibility of a major crisis required a more detailed analysis and intensified policy dialogue on the underlying macroeconomic risks in Guatemala. This report retains the macro analysis used in the policy dialogue with the Government.